Neurobiological response to EMDR therapy in clients with different psychological traumas - Pagani, Marco; Di Lorenzo, Giorgio; Monaco, Leonardo; Daverio, Andrea; Giannoudas, Ioannis; La Porta, Patrizia; Verardo, Anna R.; Niolu, Cinzia; Fernandez, Isabel; Siracusano, Alberto (Frontiers in Psychology, 2015)
We assessed cortical activation differences in real-time upon exposure to traumatic memory between two distinct groups of psychologically traumatised clients also in comparison with healthy controls. We used electroencephalography (EEG) to compare neuronal activation throughout the bilateral stimulation phase of Eye Movement Desensitization and Reprocessing (EMDR) sessions. We compared activation between the first (T0) and the last (T1) session, the latter performed after processing the index trauma. The group including all clients showed significantly higher cortical activity in orbito-frontal cortex at T0 shifting at T1 towards posterior associative regions. However the subgroup of clients with chronic exposure to the traumatic event showed a cortical firing at both stages which was closer to that of controls. For the first time EEG monitoring enabled to disclose neurobiological differences between groups of clients with different trauma histories during the reliving of the traumatic event. Cortical activations in clients chronically exposed to traumatic memories were moderate, suggesting an association between social and environmental contexts with the neurobiological response to trauma exposure and psychotherapy.